At War with the Red Badge of Courage A Critical and Cultural History. - Hayes, Kevin J. (Boydell & Brewer, Incorporated, 2021)
The story of the critical reception of Crane's great Civil War novel from its publication to the present, with particular attention to the effects of later wars on that reception.
Description based upon print version of record.
Keywords: Crane, Stephen, -- 1871-1900. -- Red badge of courage.; Red badge of courage (Crane, Stephen); United States -- History -- Civil War, 1861-1865 -- Literature and the war.; War and literature; United States; 1861-1865; History